1981
DOI: 10.1073/pnas.78.2.996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intracellular levels of calmodulin and tubulin in normal and transformed cells.

Abstract: Transformation of mammalian tissue culture cells by oncogenic viruses results in a 2-fold increase in the intracellular concentration of calmodulin quantitated by radioimmunoassay. The two pairs of companion cell lines used in this study were the Swiss mouse 3T3/simian virus 40-transformed 3T3 cells and the normal rat kidney (NRK)/Rous sarcoma virus-transformed NRK cells. The increased intracellular levels of calmodulin in the transformed cells are due to a greater increase in the rate of synthesis (3-fold) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 22 publications
4
59
0
Order By: Relevance
“…In this regard, CaM-dependent pathways represent a compelling area for investigation into the proliferative responses of malignant cells. Numerous studies have suggested the importance of CaM-mediated signalling in cell proliferation and malignant transformation (Chafouleas et al, 1981;MacManus et al, 1981;Veigl et al, 1984;Means, 1987, 1989;Lu and Means, 1993). Early studies from our laboratory and others detected increased CaM in malignant cells (Hait and DeRosa, 1988;Rasmussen and Means, 1989;Lu and Means, 1993), and demonstrated that drugs that bind directly to CaM and inhibit its function were both antiproliferative and cytotoxic to breast cancer cells (Hait and Lee, 1985;Ford et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, CaM-dependent pathways represent a compelling area for investigation into the proliferative responses of malignant cells. Numerous studies have suggested the importance of CaM-mediated signalling in cell proliferation and malignant transformation (Chafouleas et al, 1981;MacManus et al, 1981;Veigl et al, 1984;Means, 1987, 1989;Lu and Means, 1993). Early studies from our laboratory and others detected increased CaM in malignant cells (Hait and DeRosa, 1988;Rasmussen and Means, 1989;Lu and Means, 1993), and demonstrated that drugs that bind directly to CaM and inhibit its function were both antiproliferative and cytotoxic to breast cancer cells (Hait and Lee, 1985;Ford et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, calmodulin (CaM), a ubiquitous mediator of calcium-dependent signal transduction, represents a compelling area for investigation into the proliferative responses of malignant cells (Hait and Lazo, 1986;Lu and Means, 1993). For example, Chafouleas et al (1981) reported that CaM was required for re-entry of quiescent Chinese hamster ovary (CHO) cells into the cell cycle. Rasmussen and Means (1987) demonstrated that overexpression of CaM increased cell proliferation by decreasing the G 1 /S transit time, and that CaM antisense blocked this effect (Rasmussen and Means, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Chafouleas et al had clarified the true increase of CaM referring to the change of tubulin [5], an increase of the tubulin level during cell cycle has also been reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in the amount of CaM relative to total protein has been reported in chicken embryo fibroblasts transformed by Rous sarcoma virus, with CaM level quantified by either densitometric scanning of polyacrylamide gels [3] or bioassay [4], but it has not been verified if this increase was true in individual cells. In 1981,by the means of radioimmunoassay, it was reported that the transformation by oncogenic viruses resulted in an increase in the number of CaM molecules per cell by preferentially stimulating the synthesis of this protein, whereas no such elevation was observed in case of tubulin; and the increase of CaM in transformed cells amounted to 2 folds [5].…”
Section: Introductionmentioning
confidence: 99%